A Comparison of Using L1 (Indonesian) and English to Answer English Listening Comprehension Questions - Rahmah , Ismi Putri; Halimi, Sisilia Setiawati (Universitas PGRI Adi Buana Surabaya, 2020)
English test results show that a lot of Indonesian students obtained low scores in listening. Students say they understand what speakers say in an English listening test but they have difficulties in answering the questions in English. This shows that students’ English receptive skills are higher than students’ productive skills. This research intends to find out what the difference in results is when students answer English listening comprehension questions in L1 (Indonesian) and English, and what the students’ perception is on the use of Indonesian language in English listening test. This research uses the mixed method along with a listening test, questionnaires, and interview as data collection tools. The findings show that these learners have difficulties to answer the test in English. The test answered in Indonesian received better scores than in English. Moreover, the questionnaires and the interview result show positive feedback on the use of Indonesian language. This shows that the learners actually have good listening skills and that their low-test scores are mostly due to their difficulty in expressing their thoughts in English.